Reaching Out to the Millions: A 5 Key Messages Rapid IEC Campaign During the COVID-19 Pandemic. Issue 3 (April 2022) - Mudera, Cariappa P.; Bavdekar, Rohit D.; Kumar, Narinder; Veiraiah, Aravind; Nair, Ranjith K.
The ongoing COVID-19 pandemic has necessitated providing populations with simple and relevant, actionable informational messages for them to be informed on individual and community level measures to combat the pandemic. Distilling guidance from various sources into simple actionable message themes in a short time frame should be the hallmark of any rapid health promotion campaign. We developed and disseminated actionable Information, Education and Communication (IEC) messages on prevention and control during the ongoing COVID-19 pandemic by selecting five key message themes of prevention. A modified Delphi technique was used for the development process which was peer reviewed after consensus was generated. An online training model using specifically developed YouTube videos and Zoom Meetings was utilized to train Master Trainers and the further hierarchy reaching out to 6989 Community Resource Persons at the peripheral echelons. Conservatively the population reached out has been estimated to be more than 6 million (across 1.2 million households), over a two week period in April 2020. The implementing agency has created 300 videos in around 22 languages based on the 5 Key Messages, which are available online for universal access. A rapid IEC campaign that can be developed, designed and rolled out in a short span is required for emergency situations such as the ongoing pandemic. NGOs play an important role in reaching out relevant messages to the community, filling in the gaps by virtue of their relative systemic agility.